Framing consumer food demand responses in a viral pandemic. (8th May 2020) - Cranfield, John A. L.
Abstract: In this paper I explore several issues related to how the COVID‐19 pandemic might impact consumer demand for food. These impacts relate to the structure of preferences in the context of a pandemic, income and time constraints, and price effects. Discussion includes accounting for differential impacts of COVID‐19 on demand for food across sociodemographic characteristics, and several high‐level issues and observations related to where and how consumers shop and what they buy. My own thinking leads me to conclude that demand‐side factors will account for most of the changes we see in retail food market. These demand‐side effects will be dominated by income effects, the opportunity cost of time, and longer planning horizons on the part of consumers. Abstrait: Dans cet article, j′explore plusieurs questions liées à la manière dont la pandémie de COVID‐19 pourrait influer sur la demande de nourriture des consommateurs. Ces impacts sont liés à la structure des préférences dans le contexte d′une pandémie, aux contraintes de revenu et de temps et aux effets sur les prix. La discussion comprend la prise en compte des impacts différentiels de la COVID‐19 sur la demande de nourriture selon les caractéristiques sociodémographiques, ainsi que plusieurs questions et observations macros concernant l′endroit et la façon dont les consommateurs achètent et ce qu′ils achètent. Propre raisonnement m′amène à dire que les facteurs qui déterminent la demande  représentent la plupart des changements que nous voyons dans les marchés alimentaires au détail. La demande des marchés alimentaires sera dominée par les effets sur les revenus, les coûts d′opportunité de temps et les horizons de planification plus long de la part des consommateurs.